2017
DOI: 10.1007/s13187-017-1266-8
|View full text |Cite
|
Sign up to set email alerts
|

Awareness of Stomach and Colorectal Cancer Risk Factors, Symptoms and Time Taken to Seek Medical Help Among Public Attending Primary Care Setting in Muscat Governorate, Oman

Abstract: Colorectal and stomach cancers are the top ranking cancers in Oman. Most of the patients are diagnosed at advanced disease stages. The aim of this study is to explore the knowledge of risk factors, symptoms and the time needed to seek medical care for stomach cancer and colorectal cancer (CRC) among Omani participants attending 28 local health centres (LHCs) in the governorate of Muscat, the capital city of Oman. The Bowel Cancer/CRC Awareness Measure (CAM) questionnaire (translated into Arabic) was used to co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
39
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(47 citation statements)
references
References 38 publications
5
39
0
2
Order By: Relevance
“…While the majority of participants in the present study were willing to participate in CRC screening if recommended by doctors, they were nevertheless unaware of either the importance or availability of CRC screening measures in Oman. A previous study conducted in Oman similarly found that more than half of the participants would have a colonoscopy if doctors advised them to do so (Al-Azri et al, 2019). Furthermore, the majority of participants in the present study were of the belief that only doctors had the authority to request CRC screening measures.…”
Section: Discussionmentioning
confidence: 48%
See 2 more Smart Citations
“…While the majority of participants in the present study were willing to participate in CRC screening if recommended by doctors, they were nevertheless unaware of either the importance or availability of CRC screening measures in Oman. A previous study conducted in Oman similarly found that more than half of the participants would have a colonoscopy if doctors advised them to do so (Al-Azri et al, 2019). Furthermore, the majority of participants in the present study were of the belief that only doctors had the authority to request CRC screening measures.…”
Section: Discussionmentioning
confidence: 48%
“…However, a previous study conducted in Oman found that the majority of members of the public were not aware of CRC symptoms (Al-Azri et al, 2019). Alarmingly, they also reported several emotional barriers to seeking early medical help, including being worried about what the doctor might find or for wasting the doctor's time, feeling too scared or embarrassed to seek help and not feeling confident when talking about their symptoms (Al-Azri et al, 2019). Attitudes toward CRC screening are a reliable predictor of help-seeking behaviors (Rogers et al, 2018).…”
Section: Attitudes Toward and Knowledge Of Colorectal Cancer Screeninmentioning
confidence: 96%
See 1 more Smart Citation
“…Furthermore, there are currently no screening programs available for cancer, except for breast cancer, as a program was introduced in 2010 (Ministry of Health, 2010). Previous studies among the adult Omani population have shown that the majority of the public were not aware of the risk factors and symptoms for most types of cancer (Al-Azri et al, 2017;Al-Azri et al, 2016;Al-Azri et al, 2014). There are also several notable social and cultural barriers contributing to the delays in cancer diagnosis, particularly among vulnerable groups (Al-Azri et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Colon cancer is a usually malignant tumor of the digestive tract, which occurs in the colon, most commonly at the junction of the rectum and sigmoid colon (Yang et al, ). Aging of population, heredity, lifestyle, and environmental changes are the primary reasons for the high incidence of colon cancer (Al‐Azri et al, ; Fumery et al, ). The curative operation has dramatically increased the 5‐year survival rate of patients with colon cancer, whereas this cancer is a malignant tumor with highly specific, the clinical features, texture, immunophenotype, therapeutic effect, and biological course exist significant difference (Ha, Kim, Choi, & Kim, ; Tang et al, ).…”
Section: Introductionmentioning
confidence: 99%